Performance analysis of the proxy-based and collusion-resistant revocable CPABE framework - Chawla, Shobha; Gupta, Neha (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
An efficient revocation of access rights in ciphertext policy attribute-based encryption (CPABE) schemes has multiple challenges, particularly for lightweight devices. Thus, extensive research on the existing studies enforcing and governing access control has been conducted. The methodologies used in the existing CPABE (bilinear pairing cryptography based) schemes to revoke users at the system and attribute levels have been focused on in the current study. The existing studies have been examined on the basis of the following parameters for revocation: type of revocation addressed, level of collusion resistance, dynamicity achieved, scalability of revocation, and computational cost incurred. It has been observed in the study that no single scheme achieves all the revocation properties and addresses both types of revocation. The module proposed in proxy-based and collusion-resistant multi-authority revocable CPABE (PCMR-CPABE) efficiently addresses both types of revocation and is fully collusion-resistant, dynamic, and scalable. The present paper extends the study on PCMRCPABE and presents a performance analysis of the module in terms of functional specifications and computational cost. The presented analysis has compared the performance of the existing cutting-edge schemes with the PCMR-CPABE module and has proved that the proposed module is better in terms of functionality and is computationally inexpensive.